Pelatihan Pembuatan Media Pembelajaran Berbantuan OpenAI: ChatGPT Dalam Pengajaran Bahasa Inggris Bagi Guru Sekolah Menengah Pertama - Tita Wulandari; Sofendi; Alhenri Wijaya; Fiftinova; Eryansyah; Ida Rosmalina; Rita Hayati (TAAWUN, 2024)
To improve the teachers’ competencies and skills in using updated digital technology, specifically Artificial Intelligence (AI), this activity aimed at improving the teachers’ competencies and skills in creating learning media by utilizing OpenAI: ChatGPT. It is a community service done by a group of English Education Study Program lecturers at the Faculty of Teacher Training and Education, Universitas Sriwijaya. The activity procedures were program socialization, presentation, discussion, mentoring, and practices. The participants are members of the junior high school English Teachers’ Forum, in Indonesia, known as MGMP Bahasa Inggris SMP, in Lubuklinggau. Firstly, all participants were introduced to artificial intelligence and OpenAI: ChatGPT. Next, they were guided to create a new account, construct proper prompts or instructions, and integrate the platform into their English classroom. Before the workshop, the participants were given a questionnaire to answer. It was found that 100% of them never heard of or used OpenAI: ChatGPT. Nevertheless, positive responses were obtained after the workshop sessions. The participants agreed that it was really helpful for them. They can get creative teaching ideas, prepare classroom learning material, and access unlimited information. Therefore, 63,2% of the teachers strongly agree and 36,8% of the teachers agree that it can enhance the learning experience. Not only that, all participants encouraged the government or authorized institutions to give further workshops related to updated technology. As a result, the participants were able to create learning media using OpenAI: ChatGPT.